Catalytic cracking cocatalyst with high thermal wear resistance and preparation method thereof

By using high shear emulsifier to mix acid in the catalytic cracking cocatalyst, a low-collective γ-alumina precursor and clay, combined with a modifier of multi-grass chelating ligand and coordination metal, the problem of poor thermal wear resistance of existing cocatalysts is solved, and efficient catalytic cracking reaction and stable operation of long-term equipment is achieved.

CN119657211AActive Publication Date: 2025-03-21PETROCHINA CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202311224772.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-03-21
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

The existing catalytic cracking propylene and octane cocatalysts have poor thermal wear resistance due to low molecular sieve content, small pore volume and low specific surface area, which affects the smooth operation of the long-term cycle of the catalytic cracking device.

Method used

The MFI structural molecular sieve, low-collective index γ-alumina precursor and clay were used as substrates to combine multi-message ligands and coordination metal modifiers to form a catalytic cracking cocatalyst with high thermal wear resistance.

Benefits of technology

The thermal wear resistance, large pore capacity and polymer sieve content of the catalytic cracking cocatalyst are significantly improved, the stability and yield of the catalytic cracking reaction are enhanced, and the long-term stable running time of the device is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004461921200000321
    Figure BDA0004461921200000321
Patent Text Reader

Abstract

The invention discloses a catalytic cracking cocatalyst with high thermal wear resistance. The catalytic cracking cocatalyst comprises a molecular sieve, a matrix, a binder and a binder modifier, the molecular sieve has an MFI structure, and the molecular sieve with the pore diameter of less than 0.7 nm accounts for 50-100 wt% of the total amount of the molecular sieve; the matrix is composed of a gamma-alumina precursor with a peptizing index less than or equal to 50% and clay; the binder is prepared from a phosphorus-containing compound and an aluminum-containing compound; the binder modifier is prepared from the following raw materials: a polymeshed chelating ligand, precursors of at least two coordination metals, alcohol and organic acid; the binder is mixed with the binder modifier and the matrix in a high shear emulsifier. Compared with the existing catalytic cracking propylene and octane number promoter, the catalytic cracking promoter provided by the invention has higher thermal wear resistance, large pore volume and high molecular sieve content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst promoters, and in particular relates to a catalytic cracking promoter with high thermal wear resistance and a preparation method thereof. Background Art

[0002] In the catalytic cracking process, the content of the target product in the cracking product varies greatly with the different cracking catalysts and process technologies used. The use of a co-catalyst can effectively increase the yield of the target product. Propylene co-catalysts generally use MFI-type zeolites such as ZSM-5 molecular sieves as active components, kaolin as carriers, and various silica-alumina gels as binders. The introduction of phosphorus oxides into propylene and octane co-catalysts can significantly improve the activity stability of MFI-type zeolites and the selectivity of propylene in liquefied gas, and at the same time have a certain effect on improving the octane number of gasoline. Therefore, in order to improve the activity stability and propylene selectivity of the co-catalyst, phospho-alumina gel is currently generally used as a binder. In addition to having excellent propylene selectivity, phospho-alumina gel also has good bonding properties, which can meet the requirements of industrial use for catalyst strength.

[0003] However, the existing catalytic cracking propylene and octane promoters made with phosphate aluminum gel as a binder have low molecular sieve content, small pore volume, low specific surface area, poor strength, and especially poor thermal wear resistance, which leads to problems such as the target yield increase is not obvious, gasoline yield decreases, system activity deteriorates, and the strength difference with the main catalyst is obvious when used in the catalytic cracking process, which in turn causes the fluidization fluctuation of the device and affects the long-term stable operation of the device. If the content of the active component ZSM-5 molecular sieve is increased and the pore volume of the catalytic cracking propylene and octane promoter is increased, the anti-wear performance of the promoter will often deteriorate, and problems such as fluidization abnormality, agent leakage, smoke machine scaling, and increased solid content of oil slurry will occur, affecting the long-term operation of the catalytic cracking unit.

[0004] For example, Chinese patent document CN102794194B discloses a method for preparing a catalytic cracking propylene co-catalyst, including the steps of molecular sieve exchange, propylene co-catalyst preparation and propylene co-catalyst washing. The molecular sieve exchange step includes: contacting the molecular sieve with an aqueous solution containing an inorganic acid and an organic acid at 0-5°C for 0.5-2 hours; the weight ratio of H2O: molecular sieve is 5-10:1; + The organic acid concentration in the aqueous solution is 0.009-0.9 mol / L, and the inorganic acid concentration is 0.001-0.1 mol / L. The propylene co-catalyst washing step comprises: contacting the propylene co-catalyst with an aqueous solution containing an inorganic acid and an organic acid at 0-5°C for 10-100 minutes, wherein the weight ratio of H2O to propylene co-catalyst is 5-9:1, and the weight ratio of H2O to propylene co-catalyst is 1:1. +The concentration of organic acid in the aqueous solution is 0.0001-0.2 mol / L, and the concentration of inorganic acid is 0.0001-0.1 mol / L. In this scheme, the catalyst is treated with acid after being prepared and formed to achieve the purpose of optimizing the pore structure and acidity distribution of the catalyst. However, this method will reduce the cracking activity of the catalyst, especially the cracking activity of light olefins, and reduce the yield of the target product.

[0005] Chinese patent document CN103254925B discloses a catalytic cracking propylene co-catalyst and a preparation method thereof, which comprises 20-60% HZSM-5 molecular sieve, 5-25% phosphate aluminum oxide, 6-12% silica-alumina gel carrier, and the rest is kaolin, based on the total weight of the co-catalyst; the molar ratio of SiO2 to Al2O3 of the HZSM-5 molecular sieve is (25-500):1; the phosphate aluminum oxide is aluminum phosphate; and the silica-alumina gel carrier is silica-alumina gel. The co-catalyst silica-alumina sol prepared by this method will block the pores of the molecular sieve, and the pore volume in the co-catalyst is low and the specific surface area is small.

[0006] Chinese patent document CN102049284B discloses a catalytic cracking propylene catalyst, which contains 30-80% by weight of molecular sieves based on the total weight of the catalyst, wherein the content of ZSM-5 zeolite is 28-78% by weight, and the content of clay is 10-65% by weight. The catalyst contains P, which is 5.0-20.0% by weight, preferably 7.0-15.0% by weight, in terms of P2O5, and the content of La2O3 is 0-1.0% by weight; aluminum phosphate sol is used as a binder to improve the wear resistance of the catalyst and the solid content of the spray slurry, while avoiding the chlorine content on the spray slurry and the catalyst. The catalyst prepared by the method uses aluminum phosphate binder. Compared with the conventional binder silica aluminum sol, the binder makes the mesopore volume of the catalyst smaller, and the thermal wear index increases. A large amount of fine powder will be generated during the application of the device, which affects the smooth operation of the imaging device.

[0007] Chinese patent document CN107970983A discloses a co-catalyst, which comprises 10-75 wt% of phosphorus-containing MFI structure molecular sieve on a dry basis, 3-40 wt% of phosphorus-aluminum inorganic binder on a dry basis, 1-30 wt% of other inorganic binder on an oxide basis, 0-60 wt% of a second clay on a dry basis, and 0.5-15 wt% of a metal additive selected from at least one of Group VIII metals and manganese, zinc, and gallium on an oxide basis. When the method uses aluminum phosphate binder and phosphorus element to modify the molecular sieve, the introduction of excessive phosphorus in the co-catalyst will form a stable PO-Al bond with aluminum on the molecular sieve, block the pores of the molecular sieve, cause a decrease in specific surface area, and affect the reaction performance of the co-catalyst.

[0008] Chinese patent document CN104549445A discloses a method for preparing a catalytic cracking promoter, which includes preparing a high-silicon ZSM-5 molecular sieve, mixing the obtained high-silicon ZSM-5 molecular sieve with a binder and clay, and granulating the steps, wherein the preparation of the high-silicon ZSM-5 molecular sieve includes: introducing the original powder of NaZSM-5 molecular sieve into a gas-phase ultra-stable reactor, moving the original powder of NaZSM-5 molecular sieve from the molecular sieve inlet of the gas-phase ultra-stable reactor to the molecular sieve outlet of the gas-phase ultra-stable reactor without carrier gas transportation, and contacting and reacting the original powder of NaZSM-5 molecular sieve with gas-phase SiCl4 in the gas-phase ultra-stable reactor. The preparation method can continuously prepare a ZSM-5 molecular sieve with a high silicon-aluminum ratio and then prepare a catalytic cracking propylene promoter. The method first performs an ultra-stabilization treatment on the molecular sieve, and then performs an acid-base treatment, which will cause the skeleton of the molecular sieve to be severely damaged, affecting the reaction performance of the promoter.

[0009] Chinese patent document CN102847551B discloses a cracking promoter with high and low carbon olefin concentration, which contains a phosphorus aluminum inorganic binder containing a first clay, a modified MFI molecular sieve, other inorganic binders and a VIII group metal additive, with or without a second clay, wherein the phosphorus aluminum inorganic binder containing the first clay includes 15 to 40 weight % aluminum component in terms of Al2O3, 45 to 80 weight % phosphorus component in terms of P2O5 and 1 to 40 weight % of the first clay in terms of dry basis. In the preparation process of the promoter, the molecular sieve is treated with acid and alkali to expand the pore structure of the molecular sieve, which is beneficial to the increase of the pore volume and specific surface area of ​​the promoter, but the mesoporous process will reduce the crystallinity of the molecular sieve, and at the same time, a large amount of surface acid sites will be lost, resulting in a decrease in cracking reaction performance; and the molecular sieve is modified with transition metals such as P to improve its stability and reaction performance, and an aluminum phosphate binder is used, but excessive phosphorus will further reduce the reaction performance of the molecular sieve. On the other hand, conventional aluminum phosphate has poor thermal wear performance.

[0010] As mentioned above, in the prior art, a certain amount of ZSM-5 molecular sieve, silica sol or silica sol, or aluminum-containing compound is generally used as an aluminum source, and then phosphorus-containing compounds, clay and other components are added to prepare propylene co-catalysts. When the above method is used to prepare the co-catalyst, although the silicon, aluminum sol or part of the aluminum-containing compound and the phosphorus-containing compound generate part of the aluminum phosphate binder to a certain extent, it can increase the wear resistance of the catalyst, but when the molecular sieve content in the catalyst is high or the catalyst pore volume is large, its wear resistance is still insufficient. At present, the mechanism is not clear, but it has been found that when the molecular sieve content in the co-catalyst is high or the co-catalyst pore volume is large, when the co-catalyst is prepared by the existing method, the co-catalyst particles are broken to varying degrees, especially after high-temperature water vapor aging, the situation is worse. It is speculated that these ions may have a certain stable combination with the bonding component, so that the bonding component is in an inactive state. During the preparation of the co-catalyst, it is still in this inactive state, so, on the one hand, this stable combination reduces the bonding effect of the bonding component, and on the other hand, during the spray drying process of the co-catalyst, especially during the water vapor aging process, the chlorine, ammonium, and nitrate that are stably bonded to the bonding component become unstable, and generate hydrogen chloride, ammonia, nitrogen, oxygen and other gases respectively. The generation of these gases generates a large number of "bubbles" inside the co-catalyst particles. When the temperature rises, these bubbles will rush out from the inside of the co-catalyst, resulting in damage to the shape of the co-catalyst particles. In severe cases, the co-catalyst particles will rupture, thereby reducing the bonding effect of various binders and greatly reducing the anti-wear performance of the co-catalyst. On the other hand, in the preparation process of the existing propylene octane number co-catalyst, a large amount of phosphoric acid is used to modify the molecular sieve to improve the activity stability of the molecular sieve, but the use of phosphorus will react with the non-framework aluminum of the ZSM-5 molecular sieve to form a firmly bonded PO-Al bond, blocking the pores of the molecular sieve, resulting in a decrease in the crystallinity, specific surface area and activity of the ZSM-5 molecular sieve; a large amount of phosphorus will be discharged with sewage during the preparation of the co-catalyst, resulting in excessive phosphorus content in the sewage, which has an impact on the environment. Summary of the invention

[0011] In view of the problems existing in the prior art and the directions for improvement, the present invention provides a catalytic cracking co-catalyst with high thermal wear resistance and a preparation method thereof. Compared with the existing catalytic cracking propylene and octane number co-catalysts, the catalytic cracking co-catalyst provided by the present invention has higher thermal wear resistance, large pore volume and high molecular sieve content.

[0012] To achieve the above object, the present invention provides the following technical solutions:

[0013] A catalytic cracking promoter with high thermal wear resistance, comprising a molecular sieve, a matrix, a binder and a binder modifier;

[0014] The molecular sieve has an MFI structure and the molecular sieve with a pore diameter less than 0.7 nm accounts for 50wt% to 100wt% of the total molecular sieve;

[0015] The matrix is ​​composed of a γ-alumina precursor with a peptization index of ≤50% and clay;

[0016] The binder is made of a phosphorus-containing compound and an aluminum-containing compound;

[0017] The raw materials of the binder modifier include a multidentate chelating ligand, precursors of at least two coordinated metals, an alcohol and an organic acid;

[0018] The binder, the binder modifier and the matrix are mixed in a high shear emulsifier.

[0019] Optionally, the catalytic cracking promoter with high thermal wear resistance provided by the present invention further includes a molecular sieve modifier, which is the same as or different from the binder modifier; preferably, the raw materials of the molecular sieve modifier include a multi-dentate chelating ligand, a precursor of a rare earth coordination metal, an alcohol and an organic acid.

[0020] Optionally, in the catalytic cracking promoter with high thermal wear resistance provided by the present invention, the multidentate chelating ligand is a bidentate chelating ligand having at least two coordinating atoms, and the coordinating atoms are P, O, or N and O; preferably, the multidentate chelating ligand is selected from any one of aminotri (methylene phosphonic acid), hydroxyethylidene diphosphonic acid, ethylenediamine tetra (methylene phosphonic acid), diethylenetriamine penta (methylene phosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, 2-hydroxyphosphonoacetic acid, di-1,6-hexamethylenetriamine penta (methylene phosphonic acid), hexamethylenediamine tetra (methylene phosphonic acid), ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid and 1,2-ethylenediamine; more preferably, the coordinating atoms in the multidentate chelating ligand are P and O.

[0021] Optionally, in the catalytic cracking promoter with high heat wear resistance provided by the present invention, the precursor of the coordination metal in the binder modifier is selected from chlorides, sulfates or nitrates of rare earth metals and transition metals; preferably, the rare earth metal is selected from light rare earth metals, such as lanthanum, cerium, neodymium, samarium, etc.; the transition metal is selected from copper, silver, nickel, zinc, cobalt, cadmium, etc. The dosage ratio of the rare earth metal to the transition metal in the coordination metal is not specifically limited and can be adjusted according to actual conditions. The molar ratio of the transition metal to the rare earth metal recommended by the present invention is 1:5-10; the molar ratio of the multidentate chelating ligand to the coordination metal (rare earth metal and transition metal) is 2-5:1.

[0022] Optionally, in the catalytic cracking promoter with high thermal wear resistance provided by the present invention, in the molecular sieve modifier, the molar ratio of the multi-dentate chelating ligand to the rare earth coordination metal is 2 to 5:1.

[0023] Optionally, in the catalytic cracking promoter with high thermal wear resistance provided by the present invention, in the molecular sieve modifier and the binder modifier, the organic acid is one or more of benzoic acid, lactic acid, propionic acid, formic acid, acetic acid, sorbic acid and malic acid;

[0024] The alcohol is selected from C1-C3 monohydric alcohols, preferably one or more of methanol, ethanol and propanol.

[0025] Optionally, in the catalytic cracking promoter with high thermal wear resistance provided by the present invention, in the binder, the molar ratio of phosphorus in the phosphorus-containing compound to aluminum in the aluminum-containing compound is 2 to 10:1, preferably the molar ratio of phosphorus in the phosphorus-containing compound to aluminum in the aluminum-containing compound is 4 to 8:1; the aluminum-containing compound and the phosphorus-containing compound are not specifically limited, and conventional ones in the industry can be used. The aluminum-containing compound includes but is not limited to aluminum oxides, aluminum hydroxides, aluminum-containing organic compounds, etc., such as aluminum trioxide, aluminum hydroxide, boehmite sodium metaaluminate, aluminum chloride, aluminum isopropoxide, etc.; preferably aluminum oxides and aluminum hydroxides. The phosphorus-containing compound includes but is not limited to phosphorus oxides, phosphorus oxyacids, phosphoric acid, phosphates or phosphorus-containing organic matter, such as phosphoric acid, diammonium hydrogen phosphate, phosphorus pentoxide, organic phosphonic acid, sodium phosphate, calcium phosphate, etc. It is preferably phosphorus oxyacids, phosphoric acid, and phosphorus-containing ammonium salts.

[0026] Optionally, in the catalytic cracking promoter with high thermal wear resistance provided by the present invention, in the matrix, the peptization index of the γ-alumina precursor is 20% to 30%; preferably, the XRD spectrum of the γ-alumina precursor shows characteristic peaks near 2θ of 14°, 28°, 38°, and 49°; such as pseudo-boehmite, boehmite, boehmite, etc.

[0027] Optionally, in the catalytic cracking promoter with high thermal wear resistance provided by the present invention, in the matrix, the mass ratio of the γ-alumina precursor to the clay is 1:0.5-15, preferably 1:2-9.

[0028] Optionally, the clay in the matrix of the catalytic cracking promoter with high thermal wear resistance provided by the present invention can be clay commonly used in the art, which can meet the requirements of the present invention, such as one or more of kaolin, halloysite, montmorillonite, diatomite, bentonite, halloysite, etc., which are commonly used as catalytic cracking propylene, octane promoter, and catalytic cracking promoter component. Preferably, the clay is selected from kaolin, halloysite, halloysite, or a mixture thereof.

[0029] Optionally, the catalytic cracking promoter with high thermal wear resistance provided by the present invention comprises a molecular sieve comprising at least one of a BEA structure, a FER structure, a MWW structure, a MOR structure, a AST structure and a FAU structure molecular sieve; preferably, the molecular sieve is a mixed molecular sieve composed of two molecular sieves of different structures (i.e., a mixture of a MFI structure molecular sieve and any other type of molecular sieve), and the specific surface area of ​​the mixed molecular sieve is not less than 400 to 500 m 2 / g, and the Si / Al molar ratio in the MFI structured molecular sieve is 10-200.

[0030] Specifically, the molecular sieves of different structures can be conventional ones in the industry without specific limitation. For example, the molecular sieve with MFI structure can be selected from high-silicon ZSM-5, low-silicon ZSM-5, phosphorus-modified ZSM-5, ferrophosphorus-modified ZSM-5 molecular sieve or TS-1 molecular sieve, etc.; the molecular sieve with BEA structure can be selected from high-silicon Beta molecular sieve, low-silicon Beta molecular sieve and various metal-modified Beta molecular sieves, etc.; the molecular sieve with FER structure can be selected from ZSM-35 molecular sieve, etc.; the molecular sieve with MWW structure can be selected from MCM-22, MCM-41, etc.; the molecular sieve with MOR structure can be selected from mordenite, etc.; the molecular sieve with AST structure can be selected from pure silicon AST molecular sieve, etc.; the molecular sieve with FAU structure can be selected from Y-type molecular sieve, rare earth Y-type molecular sieve, dealuminated Y-type molecular sieve, ultra-stable Y-type molecular sieve, etc.

[0031] Optionally, the catalytic cracking promoter with high thermal wear resistance provided by the present invention, based on the total dry weight of the catalytic cracking promoter as 100%, the content of the molecular sieve is 20wt% to 70wt%, the content of the matrix is ​​10wt% to 40wt%, the content of the binder is 10wt% to 30wt%, the content of the binder modifier (based on the total mass of the multi-dentate chelating ligand and the coordinated metal oxide) is 1.5wt% to 10wt%, and the content of the molecular sieve modifier (based on the total mass of the multi-dentate chelating ligand and the rare earth coordinated metal oxide) is 0wt% to 2wt%.

[0032] The present invention also provides a method for preparing the above-mentioned catalytic cracking promoter with high thermal wear resistance, comprising the following steps:

[0033] Acid treatment: a molecular sieve having a Na2O content of ≤0.1wt% is mixed with deionized water to form a molecular sieve slurry, and then a mixed acid of an organic acid and an inorganic acid is added to the molecular sieve slurry until the pH value is ≤2.0 and the reaction is carried out. After the reaction is completed, the molecular sieve is dried and calcined to obtain an acid-treated molecular sieve;

[0034] Mixed slurry: the binder and the binder modifier are mixed evenly in a high shear emulsifier, and then the mixture of the acid-treated molecular sieve and deionized water is added and mixed evenly to obtain a mixed slurry;

[0035] Calcination and molding: adding the matrix slurry to the mixed slurry, and continuing to mix in a high shear emulsifier for 5 minutes, and then spray molding, drying, and calcining to obtain the catalytic cracking promoter with high thermal wear resistance.

[0036] Optionally, in the acid treatment step of the method for preparing the above-mentioned catalytic cracking promoter with high heat wear resistance provided by the present invention, when the Na2O content in the molecular sieve is greater than 0.1wt%, the step of exchanging the molecular sieve with ammonium is also included, including the following steps: exchanging the molecular sieve with ammonium salt until the Na2O content in the molecular sieve is ≤0.1wt%, separating, and drying to obtain a molecular sieve with a Na2O content of ≤0.1wt% after ammonium exchange; ammonium exchange of molecular sieve is a conventional processing process in the field, and existing conventional ammonium exchange processes can meet the implementation of the technical solution of the present invention, and are not specifically limited or introduced in detail herein.

[0037] Optionally, in the acid treatment step of the method for preparing the above-mentioned catalytic cracking promoter with high heat wear resistance provided by the present invention, the organic acid and the inorganic acid in the mixed acid of the organic acid and the inorganic acid can be conventional ones in the industry without specific limitation, such as hydrochloric acid, nitric acid, sulfuric acid, oxalic acid, citric acid, oxalic acid, tartaric acid, etc. Preferably, the pH of the system after adding the mixed acid of the organic acid and the inorganic acid is ≤1.0, and more preferably, the molar ratio of the organic acid to the inorganic acid is 2 to 5:1. The reaction device involved in this step is not specifically limited, as long as it has a reflux device, such as the reaction can be carried out in a heating kettle with a reflux device.

[0038] Optionally, in the acid treatment step of the method for preparing the above-mentioned catalytic cracking promoter with high heat wear resistance provided by the present invention, 100% water vapor is introduced in the first 2 / 3 of the calcination, and air is introduced in the last 1 / 3. The calcination under water vapor conditions in the first 2 / 3 is conducive to stabilizing the molecular sieve and improving the stability; the calcination under water vapor-free conditions in the last 1 / 3 can quickly roast out the organic matter in the promoter, and due to the space-occupying effect of the organic matter, it is conducive to forming a large number of pores in the promoter after complete calcination.

[0039] Optionally, in the acid treatment step of the method for preparing the above-mentioned catalytic cracking promoter with high thermal wear resistance provided by the present invention, the roasting parameters are not specifically limited and conventional parameters in the industry can be adopted, such as the roasting temperature can be limited to 400-800°C and the time can be limited to 2-5h.

[0040] Optionally, in the acid treatment step of the method for preparing the above-mentioned catalytic cracking promoter with high heat wear resistance provided by the present invention, after the reaction is completed, it also includes the step of adding a molecular sieve modifier; the reaction parameters after adding the molecular sieve modifier are not specifically limited, and conventional parameters in the industry can be used, such as optionally reacting at 60-100°C for 0.5-12h, preferably reacting for 3-10h.

[0041] The preparation of the molecular sieve modifier recommended by the present invention comprises the following steps:

[0042] Adding alcohol to the organic acid solution of the multidentate chelating ligand and mixing well to obtain a multidentate chelating ligand solution; preferably, the molar concentration of the multidentate chelating ligand in the multidentate chelating ligand solution is 0.1-1.0 mol / L, the concentration of the organic acid is 10wt%-30wt%, and the concentration of the alcohol is 5wt%-20wt%;

[0043] Adding alcohol to the organic acid solution of the rare earth metal precursor and mixing well to obtain the rare earth metal precursor solution; preferably, the concentration of the organic acid in the rare earth metal precursor solution is 10wt% to 30wt%, and the concentration of the alcohol is 5wt% to 20wt%;

[0044] The multidentate chelate ligand solution and the rare earth metal precursor solution are added into a high shear dispersing emulsifier, and the pH value of the system is adjusted to 5-8 to obtain a molecular sieve modifier.

[0045] Optionally, the present invention also provides a method for preparing the binder modifier, comprising the following steps:

[0046] Adding alcohol to the organic acid solution of the multidentate chelating ligand and mixing well to obtain a multidentate chelating ligand solution; preferably, the molar concentration of the multidentate chelating ligand in the multidentate chelating ligand solution is 0.15-1.0 mol / L, the concentration of the organic acid is 10wt%-30wt%, and the concentration of the alcohol is 5wt%-20wt%;

[0047] Adding alcohol to an organic acid solution containing at least two coordinated metal precursors, and mixing them to obtain a coordinated metal precursor solution; preferably, the concentration of the organic acid in the coordinated metal precursor solution is 10wt% to 30wt%, and the concentration of the alcohol is 5wt% to 20wt%;

[0048] The multi-dentate chelating ligand solution and the precursor solution of the coordination metal are added into a high shear dispersing emulsifier, and the pH value of the system is adjusted to 5-8 to obtain a binder modifier.

[0049] Optionally, the present invention also provides a method for preparing the above-mentioned binder, comprising the following steps:

[0050] The mixed aqueous solution of the phosphorus-containing compound and the aluminum-containing compound is added into a high shear emulsifier, heated to 60-80° C., and then adjusted to pH ≤ 4.0 for reaction to obtain the binder.

[0051] Optionally, in the calcination molding step of the preparation method of the above-mentioned catalytic cracking promoter with high heat wear resistance provided by the present invention, the configuration of the matrix slurry is a well-known operation in the art, specifically, the γ-alumina precursor, clay and deionized water are mixed and slurried, without special requirements. By controlling the mixing time of the mixed slurry of the molecular sieve, the aluminum phosphate binder formed in situ and the binder modifier formed in situ and the matrix slurry in the high shear emulsifier to be no more than 5 minutes, it is equivalent to achieving instantaneous full mixing, and immediately outputting and spray molding and drying after mixing, achieving the continuous "mixing, conveying, drying and molding", avoiding the long-term contact between the mixed slurry and the binder, the migration of phosphorus caused, and the reduction of the surface area and pore volume of the molecular sieve. Preferably, the mixing time of the mixed slurry and the matrix slurry in the high shear emulsifier is no more than 3 minutes.

[0052] Optionally, in the calcination molding step of the preparation method of the above-mentioned catalytic cracking promoter with high heat wear resistance provided by the present invention, the spray molding and drying refers to the granulation molding and drying of the material, which is a technology well known to those skilled in the art and can be carried out using existing parameters. For example, the preparation of catalytic cracking promoter generally uses spray molding and drying process conditions: the spray tower furnace temperature is controlled at 450-600°C, and the spray exhaust gas temperature is controlled at 150-300°C.

[0053] Preferably, the method for preparing the catalytic cracking promoter with high thermal wear resistance provided by the present invention specifically comprises the following steps:

[0054] S1: Preparation of multidentate chelating ligand solution

[0055] The multi-dentate chelating ligand is mixed with an organic acid solution to prepare an organic acid solution of the multi-dentate chelating ligand, and then an alcohol solution is added and mixed to obtain a multi-dentate chelating ligand solution;

[0056] S2: Preparation of coordinated metal precursor solution

[0057] Adding at least two coordinated metal precursors to an organic acid solution, adding an alcohol solution after the precursors are completely dissolved, and mixing them evenly to obtain a coordinated metal precursor solution;

[0058] S3: Preparation of rare earth metal precursor solution

[0059] Adding a rare earth metal precursor to an organic acid solution, adding an alcohol solution after the organic acid is completely dissolved, and mixing well to obtain a rare earth metal precursor solution;

[0060] S4: Acid treatment of molecular sieves

[0061] A molecular sieve having a Na2O content of ≤0.1wt% is mixed with deionized water to form a molecular sieve slurry, a mixed acid of an organic acid and an inorganic acid is added to make the pH of the molecular sieve slurry ≤2.0, and a reaction is carried out. After the reaction is completed, the multi-dentate chelating ligand solution prepared by S1 is added, and after stirring evenly, the rare earth metal precursor solution prepared by S3 is added to react. After the reaction is completed, the molecular sieve is dried and roasted to obtain an acid-treated molecular sieve; (when the Na2O content in the molecular sieve is greater than 0.1wt%, ammonium exchange can be carried out first to reduce the Na2O in the molecular sieve to less than 0.1wt%);

[0062] S5: Preparation of mixed slurry

[0063] Add the multi-dentate chelating ligand solution obtained in S1 to a high shear dispersing emulsifier, maintain the temperature at 30-50°C, add the coordinated metal precursor solution obtained in S2, and adjust the pH value of the system to 5-8. After the reaction is completed, a binder modifier solution is obtained. Then add a mixed aqueous solution of phosphorus-containing compounds and aluminum-containing compounds to a high shear dispersing emulsifier, heat to 60-80°C, adjust the pH value to ≤4.0 for reaction, and after the reaction is completed, a modified phosphorus-aluminum binder colloid is obtained. Then add the mixture of the acid-treated molecular sieve and deionized water in S4 to the high shear emulsifier, mix well, and obtain a mixed slurry;

[0064] S6: Preparation of matrix slurry

[0065] The matrix slurry is obtained by mixing and slurrying the γ-alumina precursor, clay and deionized water, without any special requirements;

[0066] S7: Firing and forming

[0067] The matrix slurry is added to the mixed slurry, and the mixture is continuously mixed in a high shear emulsifier for 5 minutes, and then spray-formed, dried, and calcined to obtain the catalytic cracking promoter with high thermal wear resistance.

[0068] Compared with the prior art, the present invention has the following beneficial effects:

[0069] Beneficial effect 1: In the catalytic cracking promoter provided by the present invention, the aluminum phosphate binder is modified by using a modifier containing at least two metals and a multi-dentate chelating ligand to replace the aluminum sol, silica sol, acidified pseudo-boehmite and other binders in the existing catalyst. On the one hand, it can prevent the high content of binder from clogging the pores in the promoter during the preparation of the promoter; on the other hand, it can reduce the amount of acid added during the preparation of the promoter, increase the pH value of the slurry, and then reduce the acid corrosion of the molecular sieve structure, and improve the activity of the promoter. Using a low peptization index γ-alumina precursor as one of the matrix materials, on the one hand, it can reduce the peptization of the γ-alumina precursor by the acidic medium during the preparation of the promoter, reduce the peptized alumina blocking the pores of the promoter and the pores of the zeolite molecular sieve, and accurately control the presence of free metal aluminum in the promoter system to avoid excessive reaction with the effective components of the binder, which affects the bonding performance of the binder, and the peptized small part of the γ-alumina precursor can react with the phosphorus-containing compound in the binder under specific conditions to form a binder. On the other hand, the γ-alumina precursor with a low peptization index can form a large number of mesopores during the solidification process of the co-catalyst, thereby increasing the pore volume of the co-catalyst.

[0070] Beneficial effect 2: The preparation method of the catalytic cracking promoter provided by the present invention performs a mixed treatment of inorganic acid and organic acid on the active component molecular sieve to achieve the regulation of its pore structure and morphology, increase the pore volume and specific surface area of ​​the molecular sieve; at the same time, the surface acidity of the molecular sieve is regulated to reduce the strong acid center, and the proportion of B acid and L acid. While increasing the yield of liquefied gas, the selectivity of propylene is greatly improved, and the aromatization ability is strengthened to improve the octane number of gasoline. By pre-stabilizing the molecular sieve, the molecular sieve's pore size and specific surface area are increased while the activity stability of the molecular sieve is greatly improved, and the activity retention rate under high-temperature hydrothermal conditions is improved. Therefore, in the process of preparing the co-catalyst, there is no need to introduce too much phosphorus to modify the molecular sieve, thereby reducing the reaction between phosphorus and the non-framework aluminum of the molecular sieve (if too much phosphorus is introduced during the preparation process, it will react with the non-framework aluminum of the molecular sieve to form a firmly bonded PO-Al bond, thereby blocking the pores of the molecular sieve, resulting in a decrease in the crystallinity, specific surface area and activity of the molecular sieve); in addition, since there is no need to introduce too much phosphorus in the preparation process of the co-catalyst, it can effectively avoid a large amount of phosphorus from being discharged with sewage (causing the phosphorus content in the sewage to exceed the standard), and will not cause any impact on the environment. In addition, by further using a multi-dentate chelating ligand solution and a rare earth metal precursor solution to in situ form a metal chelate, the rare earth metal can be evenly distributed on the surface of the molecular sieve to adjust the acid distribution on the surface of the molecular sieve, thereby avoiding the weakening of the strong acid centers on the surface of the molecular sieve during the acid treatment process, thereby affecting the reaction performance. At the same time, due to the occupancy effect of the metal chelate, a rich mesoporous structure can be formed during the preparation of the co-catalyst.

[0071] Beneficial effect 3: In the catalytic cracking catalyst provided by the present invention, a metal-centered ligand composed of a multi-dentate chelate ligand and at least two coordinated metals is used. Under the promotion of organic acids and alcohols, a multi-metal chelate binder modifier is prepared in situ, which is used to modify the binder. Compared with directly using commercially available metal chelates, the in-situ prepared multi-metal chelate modifier has better water solubility, can promote the combination of the modifier and the phosphorus aluminum sol, and has a better modification effect; on the other hand, the multi-dentate chelate ligand can be chelated with a variety of metal ions to form a multi-metal chelate ligand, reducing the dissolution problem between different solvents in the binder preparation process and reducing the interaction between different chelate ligands; at the same time, the ratio of different metals can be flexibly controlled to achieve the effect of accurately regulating the performance of the binder; again, the in-situ preparation of the multi-metal chelate modifier can break the limitation of the small number of commercially available metal chelates and expand the applicability of binder preparation. Finally, it is preferred to use a multi-dentate chelate ligand with N, P, and O as the coordinating atoms to reduce the introduction of too many heteroatoms into the binder, affecting the performance of the binder, and reducing the impact on the catalyst performance.

[0072] Beneficial effect 4: The preparation method of the catalytic cracking co-catalyst provided by the present invention, in-situ synthesis of a binder modifier (metal chelate) and a binder, and modification of the binder by using the binder modifier, on the one hand, can effectively avoid the introduction of molecular sieves or other heteroatoms into the binder, that is, avoid the impurities introduced in the process of forming aluminum phosphate crystals affecting the crystallinity of aluminum phosphate crystals, causing collapse under high-temperature hydrothermal conditions (that is, causing chlorine, ammonium, nitrate ions to be unable to form a strong bond with the binder, reducing the bubbles formed during the curing and roasting process, and then forming defect sites in the co-catalyst leading to collapse). On the other hand, more importantly, in the in-situ synthesis of binders and binder modifiers, the metal ions (transition metal ions and rare earth metal ions, etc.) in the binder will modify the aluminum phosphate binder, strengthen the interaction between aluminum phosphate and the matrix material and the molecular sieve, and improve the bonding strength between the binder and other components. Experiments show that the metal ions in the binder provided in the present invention can greatly improve the thermal collapse phenomenon under high-temperature hydrothermal conditions, thereby greatly improving the thermal wear performance of the co-catalyst; at the same time, it can avoid the premature hardening of the colloid during the later co-catalyst molding and drying process, and the reaction performance is reduced due to the clogging of the co-catalyst pores, thereby increasing the pore volume of the co-catalyst. A large number of test results show that when the binder modifier is added to the aluminum phosphate binder, micropores and mesopores can be formed inside the binder during the preparation process, thereby increasing the pore volume of the co-catalyst without affecting the bonding performance of the binder.

[0073] Beneficial effect 5: The preparation method of the catalytic cracking promoter provided by the present invention does not specifically limit the reaction device of the acid treatment step, as long as it can be implemented. In the preparation step of the mixed slurry and the calcination molding step, when the binder and the binder modifier are synthesized in situ and mixed with the acid-treated molecular sieve, and then mixed and emulsified with the matrix slurry, a high shear emulsifier is required. On the one hand, the low peptization index γ-alumina precursor can be dispersed into a uniform and viscous emulsion slurry, and efficiently mixed with the molecular sieve, overcoming the technical difficulties that the low peptization index γ-alumina precursor has poor solubility and cannot form a uniform slurry; at the same time, the γ-alumina precursor exists in a non-free state to avoid transitional reaction with the phosphorus-containing compounds in the binder. On the other hand, the use of a high shear emulsifier solves the problem that the binder modifier and the aluminum phosphate binder cannot be fully mixed, promotes the mutual reaction between the aluminum phosphate binder and the binder modifier, effectively regulates the microenvironment such as the supersaturation distribution in the reactor, and improves the role of the metal chelate of the binder modification component. More importantly, the application of high shear emulsifier achieves short-time and efficient mixing of binder modifier, binder, molecular sieve and matrix slurry, achieves emulsification of low peptization index γ-alumina precursor in a short time, and fully homogenizes binder, binder modifier, molecular sieve and matrix slurry; after uniform mixing, spray drying is immediately carried out to avoid phosphorus migration caused by long-term contact between binder and molecular sieve, and achieves the encapsulation and positioning of phosphorus in aluminum phosphate binder. It plays an irreplaceable role in improving the reaction performance of the co-catalyst. DETAILED DESCRIPTION

[0074] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.

[0075] If no specific experimental steps or conditions are specified in the examples and comparative examples, the conventional experimental steps or conditions described in the literature in the art can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.

[0076] The raw materials and equipment involved in the present invention are all commercially available and can meet the implementation of the technical solution of the present invention. However, for the convenience of comparison, the following raw materials are used in the following examples:

[0077] Y-type molecular sieve, ZSM-5 molecular sieve, Beta molecular sieve, MCM-22 molecular sieve, collected from Lanzhou Petrochemical Company;

[0078] Hydrochloric acid, citric acid, nitric acid, oxalic acid, phosphoric acid, aluminum hydroxide, aluminum oxide, aluminum dihydrogen phosphate, diammonium hydrogen phosphate, aluminum chloride, phosphonic acid, aluminum nitrate, aluminum isopropoxide, hexamethylenediaminetetramethylenephosphonic acid, benzoic acid, 1-propanol, nickel nitrate, zinc sulfate, neodymium sulfate, lactic acid, cobalt chloride, samarium chloride, 1,2-ethylenediamine, ethylenediaminetetraacetic acid, hydroxyethylidene diphosphonic acid, hexamethylenediaminetetramethylenephosphonic acid, diethylenetriaminepenta(methylenephosphonic acid), formic acid, acetic acid, ethanol, copper nitrate, lanthanum chloride, lanthanum nitrate, silver nitrate, cerium nitrate, propionic acid, methanol, ethylenediaminetetraacetic acid chelated copper, hydroxyethylethylenediaminetriacetic acid chelated lanthanum; all are analytically pure and produced by Sinopharm Group;

[0079] Pseudo-boehmite, boehmite, kaolin, halloysite, diatomaceous earth, bentonite, produced by China Aluminum Shandong Aluminum Co., Ltd.

[0080] Evaluation and analysis methods:

[0081] The surface area of ​​the co-catalyst was determined by low temperature nitrogen adsorption-desorption method (NB / SH / T 0959);

[0082] The pore volume of the co-catalyst was tested using the water drop method (NB / SH / T 0955);

[0083] The wear index of the co-catalyst was determined by the straight tube method (NB / SH / T 0964);

[0084] The thermal collapse rate of the catalyst promoter was tested on a laboratory small fixed fluidized bed (all parts are made of stainless steel) wear system. The specific steps are as follows:

[0085] The catalyst promoter in the fluidized bed is constantly fluidized and worn under the action of fluidized air. The extremely fine powder particles under wear flow out of the fluidized bed through the filter element with the gas, while the larger particles are blocked by the filter element and remain in the fluidized bed to continue to wear. There are 5 air inlet holes evenly distributed at the front end and around the air guide tube, with an aperture of 1mm, and the filtration accuracy of the filter element is 1μm. During the experiment, first weigh 100g of the prepared catalyst promoter, recorded as w1, and then add it to the fluidized bed, heat the preheater to 150℃, the fluidized bed temperature to 200℃, turn on the air generator, adjust the gas flow rate to 40m / s, and the apparent gas velocity in the reactor to 0.8m / s. After 4h of fluidized wear, weigh the remaining catalyst mass in the reactor and record it as w2, change the preheater temperature to 650℃, the fluidized bed temperature to 680℃, and repeat the measurement of the remaining catalyst weight under other conditions, recorded as w3, then the thermal collapse rate L is:

[0086] L=(w2-w3) / w2×100%

[0087] The catalyst reaction performance was tested using a small fixed fluidized bed microreactor according to the NB / SH / T0952-2017 method.

[0088] Example 1

[0089] The catalytic cracking promoter provided in this embodiment, based on the total weight of the catalytic cracking promoter on a dry basis as 100%, has a ZSM-5 molecular sieve (Si / Al (mol) = 10) content of 10wt%, a Y-type molecular sieve content of 10wt%, a binder modifier content (based on the total mass of the multi-dentate chelating ligand and the coordinated metal oxide) of 9wt%, a pseudo-boehmite content (peptization index of 20%) of 26.5wt%, a kaolin content of 13.5wt%, a binder content of 30wt% (P / Al molar ratio of 2:1), and a molecular sieve modifier content (based on the total mass of the multi-dentate chelating ligand and the rare earth metal oxide) of 1wt%.

[0090] The specific preparation method is as follows:

[0091] S1: Mixing bidentate chelating ligand 1,2-ethylenediamine with formic acid solution to prepare formic acid solution of multidentate chelating ligand, adding methanol solution after mixing evenly to prepare 1,2-ethylenediamine ligand solution. The molar concentration of 1,2-ethylenediamine in the solution is 0.2 mol / L, the concentration of formic acid is 30wt%, and the concentration of methanol is 20wt%.

[0092] S2: Add lanthanum chloride and copper nitrate to a formic acid solution, add a methanol solution after they are completely dissolved, and mix them evenly to obtain a precursor solution of a mixed coordination metal. The concentration of formic acid in the precursor solution is 30wt%, the concentration of methanol is 20wt%, the total molar concentration of the coordination metal (lanthanum and copper) is 0.1mol / L, and the molar ratio of lanthanum chloride to copper nitrate is 5:1.

[0093] S3: adding lanthanum chloride to a formic acid solution, adding an ethanol solution after the lanthanum chloride is completely dissolved, and mixing to obtain a lanthanum chloride solution. The concentration of formic acid in the solution is 30wt%, the concentration of ethanol is 20wt%, and the molar concentration of lanthanum is 0.1mol / L.

[0094] S4: After exchanging the ZSM-5 molecular sieve and the Y-type molecular sieve with ammonium chloride, the molar content of Na2O in the mixed molecular sieve is reduced to below 0.1wt%.

[0095] S5: Mix the mixed molecular sieve after the ammonium exchange with deionized water to obtain a molecular sieve slurry, and then add a mixture of dilute hydrochloric acid and citric acid (the molar ratio of hydrochloric acid to citric acid is 2:1) to the molecular sieve slurry. After the addition of the acid, the pH of the system is 2.0, and the temperature is raised to 60°C. After reacting in a reactor with a reflux device for 12 hours until the reaction is completed, the 1,2-ethylenediamine ligand solution prepared by S1 is added, and after stirring evenly, the lanthanum chloride solution prepared by S3 is added. After continuing to stir at the same temperature for 1 hour, the material obtained after the reaction is dried at 120°C for 12 hours, and then roasted at 400°C for 5 hours (100% water vapor is introduced for the first 200 minutes of roasting, and air is introduced for the last 100 minutes of roasting) to obtain an acid-treated molecular sieve;

[0096] Wherein, the molar ratio of 1,2-ethylenediamine to lanthanum chloride is 2:1.

[0097] S6: Add the 1,2-ethylenediamine ligand solution obtained in S1 to a high shear dispersing emulsifier, keep the temperature at 30°C, add an equal volume of the mixed coordination metal precursor solution obtained in S2, adjust the pH value of the system to 5, and obtain a binder modifier solution. Then add a mixed aqueous solution of aluminum hydroxide and aluminum dihydrogen phosphate (P / Al molar ratio is 2:1) to the binder modifier solution, and heat it to 60°C in a high shear dispersing emulsifier, adjust the pH to 4.0 for reaction, and after the reaction is completed, a modified aluminum phosphate binder colloid can be obtained. Then mix the acid-treated molecular sieve obtained in S5 with deionized water, add it to a high shear emulsifier, and mix well to obtain a mixed slurry;

[0098] S7: Pseudo-boehmite (peptization index is 20%), kaolin and deionized water are mixed to prepare a matrix slurry.

[0099] S8: Add the mixed slurry prepared in S6 to the base slurry prepared in S7, and continue mixing in a high shear emulsifier for 2 minutes, and then spray forming. The spray forming conditions are that the furnace temperature of the spray tower is controlled at 580°C, and the spray exhaust temperature is controlled at 160°C. The obtained material is calcined at 600°C for 2 hours to obtain a catalytic cracking promoter.

[0100] The physical and chemical properties and catalytic performance of the catalytic cracking promoter are specifically shown in Table 1.

[0101] Example 2

[0102] The catalytic cracking promoter provided in this embodiment, based on the total weight of the catalytic cracking promoter on a dry basis as 100%, has a ZSM-5 molecular sieve (Si / Al (mol) = 50) content of 49wt%, a Beta molecular sieve content of 21wt%, a binder modifier content (based on the total mass of the multidentate chelating ligand and the coordinated metal oxide) of 1.5wt%, a boehmite content (peptization index 30%) of 3.5wt%, a halloysite content of 6.5wt%, a binder content of 18wt% (P / Al molar ratio of 10:1); and a molecular sieve modifier content (based on the total mass of the multidentate chelating ligand and the rare earth metal oxide) of 0.5wt%.

[0103] The specific preparation method is as follows:

[0104] S1: Mixing the hexadentate chelating ligand ethylenediaminetetraacetic acid with an acetic acid solution to prepare an acetic acid solution of the ethylenediaminetetraacetic acid multidentate chelating ligand, and adding an ethanol solution after mixing evenly to prepare an ethylenediaminetetraacetic acid ligand solution. The molar concentration of the ethylenediaminetetraacetic acid in the ligand solution is 1 mol / L, the concentration of the organic acid in the solution is 10wt%, and the concentration of the ethanol is 5wt%.

[0105] S2: adding cerium nitrate and silver nitrate to an acetic acid solution, adding an ethanol solution after they are completely dissolved, and mixing them evenly to obtain a precursor solution of a mixed coordination metal. The concentration of acetic acid in the precursor solution is 10wt%, the concentration of ethanol is 5wt%, the total molar concentration of the coordination metal (cerium and silver) is 0.2mol / L, and the molar ratio of cerium nitrate to silver nitrate is 10:1.

[0106] S3: adding cerium nitrate to acetic acid solution, adding ethanol solution after complete dissolution, and mixing evenly to obtain cerium nitrate solution, wherein the concentration of acetic acid in the solution is 30wt%, the concentration of ethanol is 20wt%, and the molar concentration of cerium is 0.2mol / L.

[0107] S4: Mix a mixed molecular sieve of ZSM-5 and Beta molecular sieve with deionized water to obtain a molecular sieve slurry, and then add a mixture of dilute nitric acid and oxalic acid (the molar ratio of dilute nitric acid to oxalic acid is 5:1) to the molecular sieve slurry. After adding the acid, the pH of the system is 0.5, and the temperature is raised to 80°C. After reacting for 3 hours in a reactor with a reflux device until the reaction is completed, the ethylenediaminetetraacetic acid ligand solution prepared by S1 is added, and after stirring evenly, an equal volume of cerium nitrate solution prepared by S3 is added. After continuing to stir at the same temperature for 1 hour, the material obtained after the reaction is dried at 120°C for 12 hours, and then roasted at 800°C for 2 hours (100% water vapor is introduced for the first 80 minutes of roasting, and air is introduced for the last 40 minutes of roasting) to obtain an acid-treated molecular sieve;

[0108] Wherein, the molar ratio of ethylenediaminetetraacetic acid to cerium nitrate is 5:1.

[0109] S5: Add the ethylenediaminetetraacetic acid solution obtained in S1 to a high shear dispersing emulsifier, keep the temperature at 50°C, add an equal volume of the mixed coordination metal precursor solution obtained in S2, adjust the pH value of the system to 5, and obtain a binder modifier solution. Then add a mixed aqueous solution of aluminum oxide and phosphoric acid (P / Al molar ratio = 10:1) to the binder modifier solution, and heat it to 80°C in a high shear dispersing emulsifier, adjust the pH to 3.0 for reaction, and after the reaction is completed, a modified aluminum phosphate binder colloid can be obtained. Then mix the acid-treated molecular sieve obtained in S4 with deionized water, add it to the high shear emulsifier, and mix well to obtain a mixed slurry;

[0110] S6: Boehmite (peptization index 30%), argonite and deionized water are mixed to prepare a matrix slurry.

[0111] S7: Add the mixed slurry prepared in S5 to the base slurry prepared in S6, and continue mixing in a high shear emulsifier for 4 minutes, and then spray forming. The spray forming conditions are as follows: the furnace temperature of the spray tower is controlled at 580°C, and the spray exhaust temperature is controlled at 160°C. The obtained material is calcined at 600°C for 2 hours to obtain a catalytic cracking promoter.

[0112] The physical and chemical properties and catalytic performance of the catalytic cracking promoter are specifically shown in Table 1.

[0113] Example 3

[0114] The catalytic cracking promoter provided in this embodiment, based on the total weight of the catalytic cracking promoter on a dry basis as 100%, has a ZSM-5 molecular sieve (Si / Al (mol) = 200) content of 26wt%, a MCM-22 molecular sieve content of 11wt%, a binder modifier content (based on the total mass of the multidentate chelating ligand and the coordinated metal oxide) of 6.4wt%, a pseudo-boehmite (peptization index 25%) content of 2.2wt%, a diatomaceous earth content of 32.8wt%, a binder content of 20wt% (P / Al molar ratio of 5:1); and a molecular sieve modifier content (based on the total mass of the multidentate chelating ligand and the rare earth metal oxide) of 1.6wt%.

[0115] The specific preparation method is as follows:

[0116] S1: Mixing a tetradentate chelating ligand hydroxyethylidene diphosphonic acid with a propionic acid solution to prepare a propionic acid solution of a hydroxyethylidene diphosphonic acid multidentate chelating ligand, and adding a methanol solution after mixing evenly to prepare a hydroxyethylidene diphosphonic acid ligand solution. The molar concentration of hydroxyethylidene diphosphonic acid in the ligand solution is 0.6 mol / L, the concentration of propionic acid is 20 wt%, and the concentration of methanol is 10 wt%.

[0117] S2: Add neodymium sulfate and zinc sulfate to a propionic acid solution, add an ethanol solution after they are completely dissolved, and mix them evenly to obtain a precursor solution of a mixed coordination metal. The concentration of propionic acid in the precursor solution is 20wt%, the concentration of ethanol is 10wt%, the total molar concentration of the coordination metals (neodymium and zinc) is 0.2mol / L, and the molar ratio of zinc sulfate to neodymium sulfate is 1:8.

[0118] S3: Adding neodymium sulfate to the propionic acid solution, adding ethanol solution after it is completely dissolved, and mixing well to obtain a neodymium sulfate solution. The concentration of propionic acid in the solution is 20wt%, the concentration of ethanol is 10wt%, and the molar concentration of neodymium is 0.2mol / L.

[0119] S4: Mixing a mixed molecular sieve of ZSM-5 and MCM-22 molecular sieve with deionized water to obtain a molecular sieve slurry, and then adding a mixture of dilute nitric acid and citric acid (the molar ratio of nitric acid to citric acid is 3:1) to the molecular sieve slurry. After adding the acid, the pH of the system is 1.0, and the temperature is raised to 80°C. After reacting for 6 hours in a reactor with a reflux device until the reaction is completed, the hydroxyethylidene diphosphonic acid ligand solution prepared by S1 is added, and after stirring evenly, an equal volume of the neodymium sulfate solution prepared by S3 is added. After continuing to stir at the same temperature for 0.5 hours, the material obtained after the reaction is dried at 120°C for 12 hours, and then roasted at 600°C for 3 hours (100% water vapor is introduced into the first 120 minutes of roasting, and air is introduced into the last 60 minutes for roasting) to obtain an acid-treated molecular sieve;

[0120] Wherein, the molar ratio of hydroxyethylidene diphosphonic acid to neodymium sulfate is 3:1.

[0121] S5: Add the hydroxyethylidene diphosphonic acid ligand solution obtained in S1 to a high shear dispersing emulsifier, keep the temperature at 40°C, add an equal volume of the mixed coordination metal precursor solution obtained in S2, adjust the pH value of the system to 7, and obtain a binder modifier solution. Add a mixed aqueous solution of aluminum chloride and organic phosphonic acid (P / Al molar ratio = 5:1) to a high shear dispersing emulsifier, heat to 80°C, adjust the pH to 3.0 for reaction, and after the reaction is completed, a modified aluminum phosphate binder colloid can be obtained. Then mix the acid-treated molecular sieve obtained in S4 with deionized water, add it to a high shear emulsifier, and mix well to obtain a mixed slurry;

[0122] S6: Pseudo-boehmite (peptization index 25%), diatomaceous earth and deionized water are mixed to prepare a matrix slurry.

[0123] S7: Add the mixed slurry prepared in S5 to the base slurry prepared in S6, and continue mixing in a high shear emulsifier for 1 minute, and then spray forming. The spray forming conditions are that the furnace temperature of the spray tower is controlled at 580°C, and the spray exhaust temperature is controlled at 160°C. The obtained material is calcined at 600°C for 2 hours to obtain a catalytic cracking promoter.

[0124] The physical and chemical properties and catalytic performance of the catalytic cracking promoter are specifically shown in Table 1.

[0125] Example 4

[0126] The catalytic cracking promoter provided in this embodiment, based on the total weight of the catalytic cracking promoter on a dry basis as 100%, has a ZSM-5 molecular sieve (Si / Al (mol) = 100) content of 35wt%, a Y-type molecular sieve content of 9wt%, a binder modifier content (based on the total mass of the multi-dentate chelating ligand and the coordinated metal oxide) of 2.8wt%, a boehmite content (peptization index of 25%) of 3.6wt%, a bentonite content of 33.4wt%, a binder content of 15wt% (P / Al molar ratio of 8:1); and a molecular sieve modifier content (based on the total mass of the multi-dentate chelating ligand and the rare earth metal oxide) of 0.8wt%.

[0127] The specific preparation method is as follows:

[0128] S1: Mixing tetradentate chelating ligand hexamethylenediaminetetramethylenephosphonic acid with benzoic acid solution to prepare benzoic acid solution of hexamethylenediaminetetramethylenephosphonic acid multidentate chelating ligand, adding ethanol solution after mixing evenly to prepare hexamethylenediaminetetramethylenephosphonic acid ligand solution. The molar concentration of hexamethylenediaminetetramethylenephosphonic acid in the solution is 0.6 mol / L, the concentration of benzoic acid is 20 wt%, and the concentration of ethanol is 10 wt%.

[0129] S2: Add nickel nitrate and neodymium sulfate to benzoic acid solution, add 1-propanol solution after complete dissolution, mix well to obtain a precursor solution of mixed coordination metals. The concentration of benzoic acid in the precursor solution is 20%, the concentration of 1-propanol is 10%, the total molar concentration of coordination metals (nickel and neodymium) is 0.2 mol / L, and the molar ratio of nickel nitrate to neodymium sulfate is 1:6.

[0130] S3: Add neodymium sulfate to the benzoic acid solution, add 1-propanol solution after it is completely dissolved, and mix well to obtain a precursor solution of rare earth metals. The concentration of benzoic acid in the precursor solution is 20%, the concentration of 1-propanol is 10%, and the molar concentration of neodymium sulfate is 0.2 mol / L.

[0131] S4: After exchanging the ZSM-5 molecular sieve and the Y-type molecular sieve with ammonium chloride, the molar content of Na2O in the mixed molecular sieve is reduced to below 0.1wt%.

[0132] S5: Mix a mixed molecular sieve of ZSM-5 molecular sieve and Y molecular sieve with deionized water to obtain a molecular sieve slurry, and then add a mixture of dilute hydrochloric acid and tartaric acid (the molar ratio of hydrochloric acid to tartaric acid is 3:1) to the molecular sieve slurry. After adding the acid, the pH of the system is 0.5, and the temperature is raised to 80°C. After reacting in a reactor with a reflux device for 10 hours until the reaction is completed, the hexamethylenediaminetetramethylenephosphonic acid ligand solution prepared by S1 is added, and after stirring evenly, an equal volume of the rare earth metal precursor solution prepared by S3 is added. After continuing to stir at the same temperature for 0.5 hours, the material obtained after the reaction is dried at 80°C for 10 hours, and then roasted at 600°C for 3 hours (100% water vapor is introduced for the first 120 minutes of roasting, and air is introduced for the last 60 minutes of roasting) to obtain an acid-treated molecular sieve;

[0133] Wherein, the molar ratio of hexamethylenediaminetetramethylenephosphonic acid to neodymium sulfate is 3:1.

[0134] S6: Add the hexamethylenediaminetetramethylenephosphonic acid solution obtained in S1 to a high shear dispersing emulsifier, maintain the temperature at 40°C, add an equal volume of the mixed coordination metal precursor solution obtained in S2, adjust the pH value of the system to 7, and obtain a binder modifier solution. Add a mixed aqueous solution of aluminum nitrate and diammonium hydrogen phosphate (P / Al molar ratio = 8:1) to a high shear dispersing emulsifier, heat to 70°C, adjust the pH to 3.0, and react. After the reaction is completed, a modified aluminum phosphate binder colloid can be obtained. Then mix the acid-treated molecular sieve obtained in S5 with deionized water, add it to a high shear emulsifier, and mix well to obtain a mixed slurry;

[0135] S7: Boehmite (peptization index is 25%), bentonite and deionized water are mixed to prepare a matrix slurry.

[0136] S8: Add the mixed slurry prepared in S6 to the base slurry prepared in S7, and continue mixing in a high shear emulsifier for 1 minute, and then spray forming. The spray forming conditions are as follows: the furnace temperature of the spray tower is controlled at 580°C, and the spray exhaust gas temperature is controlled at 160°C. The obtained material is calcined at 600°C for 2 hours to obtain a catalytic cracking promoter.

[0137] The physical and chemical properties and catalytic performance of the catalytic cracking promoter are specifically shown in Table 1.

[0138] Example 5

[0139] The catalytic cracking promoter provided in this embodiment, based on the total weight of the catalytic cracking promoter on a dry basis as 100%, has a ZSM-5 molecular sieve content of 45wt%, a Y-type molecular sieve content of 11wt%, a binder modifier content (based on the total mass of the multi-dentate chelating ligand and the coordinated metal oxide) of 2.4wt%, a pseudo-boehmite content (peptization index of 25%) of 4wt%, a kaolin content of 27wt%, a binder content of 10wt% (P / Al molar ratio of 6:1), and a molecular sieve modifier content (based on the total mass of the multi-dentate chelating ligand and the rare earth metal oxide) of 0.6wt%.

[0140] The specific preparation method is as follows:

[0141] S1: Mixing the octadent chelating ligand diethylenetriamine penta (methylene phosphonic acid) with the lactic acid solution to prepare a lactic acid solution of the diethylenetriamine penta (methylene phosphonic acid) multidentate chelating ligand, and adding the ethanol solution after mixing evenly to prepare a diethylenetriamine penta (methylene phosphonic acid) ligand solution. The molar concentration of the diethylenetriamine penta (methylene phosphonic acid) in the ligand solution is 0.6 mol / L, the concentration of the lactic acid is 20%, and the concentration of the ethanol is 10%.

[0142] S2: Add samarium chloride and cobalt chloride to a lactic acid solution, add an ethanol solution after they are completely dissolved, and mix them evenly to obtain a precursor solution of a mixed coordination metal. The concentration of lactic acid in the precursor solution is 20%, the concentration of ethanol is 10%, the total molar concentration of the coordination metals (samarium and cobalt) is 0.15 mol / L, and the molar ratio of cobalt chloride to samarium chloride is 1:8.

[0143] S3: Add samarium chloride to the lactic acid solution, add ethanol solution after it is completely dissolved, mix well to obtain a precursor solution of rare earth metals. The concentration of lactic acid in the precursor solution is 20%, the concentration of ethanol is 10%, and the molar concentration of samarium is 0.15 mol / L.

[0144] S4: After exchanging the ZSM-5 molecular sieve and the Y-type molecular sieve with ammonium chloride, the molar content of Na2O in the mixed molecular sieve is reduced to below 0.1wt%.

[0145] S5: Mix the mixed molecular sieve of ZSM-5 molecular sieve and Y-type molecular sieve with deionized water to obtain molecular sieve slurry, and then add a mixture of dilute hydrochloric acid and oxalic acid (the molar ratio of hydrochloric acid to oxalic acid is 3:1) to the molecular sieve slurry. After adding the acid, the system pH is 1.0, and the temperature is raised to 80°C. After reacting in a reactor with a reflux device for 2 hours until the reaction is completed, add the diethylenetriamine penta (methylene phosphonic acid) ligand solution prepared by S1, stir evenly, add an equal volume of the rare earth metal precursor solution prepared by S3, and continue to stir at this temperature for 0.5 hours. The material obtained after the reaction is dried at 120°C for 12 hours, and then roasted at 600°C for 3 hours (100% water vapor is passed in the first 120 minutes of roasting, and air is passed in the last 60 minutes for roasting) to obtain the acid-treated molecular sieve;

[0146] Wherein, the molar ratio of diethylenetriaminepenta(methylenephosphonic acid) to samarium chloride is 4:1.

[0147] S6: Add the hexamethylenediaminetetramethylenephosphonic acid ligand solution obtained in S1 to a high shear dispersing emulsifier, keep the temperature at 40°C, add an equal volume of the mixed coordination metal precursor solution obtained in S2, adjust the pH value of the system to 7, and obtain a binder modifier solution. Add a mixed aqueous solution of aluminum isopropoxide and phosphoric acid (P / Al molar ratio = 6:1) to a high shear dispersing emulsifier, heat to 70°C, adjust the pH to 3.0 for reaction, and after the reaction is completed, a modified aluminum phosphate binder colloid can be obtained. Then mix the acid-treated molecular sieve obtained in S5 with deionized water, add it to a high shear emulsifier, and mix well to obtain a mixed slurry;

[0148] S7: Pseudo-boehmite (peptization index is 25%), kaolin and deionized water are mixed to prepare a matrix slurry.

[0149] S8: Add the mixed slurry prepared in S6 to the base slurry prepared in S7, and continue mixing in a high shear emulsifier for 1 minute, and then spray forming. The spray forming conditions are as follows: the furnace temperature of the spray tower is controlled at 580°C, and the spray exhaust gas temperature is controlled at 160°C. The obtained material is calcined at 600°C for 2 hours to obtain a catalytic cracking promoter.

[0150] The physical and chemical properties and catalytic performance of the catalytic cracking promoter are specifically shown in Table 1.

[0151] Example 6

[0152] The catalytic cracking promoter provided in this embodiment, based on the total weight of the catalytic cracking promoter on a dry basis as 100%, has a ZSM-5 molecular sieve content of 45wt%, a Y-type molecular sieve content of 11wt%, a binder modifier content (based on the total mass of the multi-dentate chelating ligand and the coordinated metal oxide) of 3.0wt%, a pseudo-boehmite (peptization index of 25%) content of 4wt%, a kaolin content of 27wt%, and a binder content of 10wt% (P / Al molar ratio of 6:1).

[0153] The specific preparation method is as follows:

[0154] S1: Mixing the octadent chelating ligand diethylenetriamine penta (methylene phosphonic acid) with the lactic acid solution to prepare a lactic acid solution of the diethylenetriamine penta (methylene phosphonic acid) multidentate chelating ligand, and adding the ethanol solution after mixing evenly to prepare a diethylenetriamine penta (methylene phosphonic acid) ligand solution. The molar concentration of the diethylenetriamine penta (methylene phosphonic acid) in the ligand solution is 0.6 mol / L, the concentration of the lactic acid is 20%, and the concentration of the ethanol is 10%.

[0155] S2: Add samarium chloride and cobalt chloride to a lactic acid solution, add an ethanol solution after they are completely dissolved, and mix them evenly to obtain a precursor solution of a mixed coordination metal. The concentration of lactic acid in the precursor solution is 20%, the concentration of ethanol is 10%, the total molar concentration of the coordination metals (samarium and cobalt) is 0.15 mol / L, and the molar ratio of cobalt chloride to samarium chloride is 1:8.

[0156] S3: After exchanging the ZSM-5 molecular sieve and the Y-type molecular sieve with ammonium chloride, the molar content of Na2O in the mixed molecular sieve is reduced to below 0.1wt%.

[0157] S4: Mix the mixed molecular sieve of ZSM-5 molecular sieve and Y-type molecular sieve with deionized water to obtain molecular sieve slurry, and then add a mixture of dilute hydrochloric acid and oxalic acid (the molar ratio of hydrochloric acid to oxalic acid is 3:1) to the molecular sieve slurry. After adding the acid, the pH of the system is 1.0, and the temperature is raised to 80°C. React in a reactor with a reflux device for 2 hours until the reaction is completed. The material obtained after the reaction is dried at 120°C for 12 hours, and then roasted at 600°C for 3 hours (100% water vapor is passed in the first 120 minutes of roasting, and air is passed in the last 60 minutes for roasting) to obtain the acid-treated molecular sieve;

[0158] S5: Add the hexamethylenediaminetetramethylenephosphonic acid ligand solution obtained in S1 to a high shear dispersing emulsifier, keep the temperature at 40°C, add an equal volume of the mixed coordination metal precursor solution obtained in S2, adjust the pH value of the system to 7, and obtain a binder modifier solution. Add a mixed aqueous solution of aluminum isopropoxide and phosphoric acid (P / Al molar ratio = 6:1) to a high shear dispersing emulsifier, heat to 70°C, adjust the pH to 3.0 for reaction, and after the reaction is completed, a modified aluminum phosphate binder colloid can be obtained. Then mix the acid-treated molecular sieve obtained in S5 with deionized water, add it to a high shear emulsifier, and mix well to obtain a mixed slurry;

[0159] S6: Pseudo-boehmite (peptization index is 25%), kaolin and deionized water are mixed to prepare a matrix slurry.

[0160] S7: Add the mixed slurry prepared in S5 to the matrix slurry prepared in S, and continue mixing in a high shear emulsifier for 1 minute, and then spray forming. The spray forming conditions are that the furnace temperature of the spray tower is controlled at 580°C, and the spray exhaust gas temperature is controlled at 160°C. The obtained material is calcined at 600°C for 2 hours to obtain a catalytic cracking promoter.

[0161] The physical and chemical properties and catalytic performance of the catalytic cracking promoter are specifically shown in Table 1.

[0162] Comparative Example 1

[0163] The catalytic cracking promoter provided in this comparative example contains 70wt% of molecular sieves, based on the total weight of the promoter on dry basis as 100%, wherein the content of ZSM-5 zeolite (Si / Al (mol) ratio is 50) is 49wt%, and the content of Beta molecular sieve is 21wt%; it contains 10wt% of kaolin, 4wt% of pseudo-boehmite (peptization index 99%), the promoter (calculated as P2O5) is 15wt%, and the content of La2O3 is 1.0wt%.

[0164] Preparation of phosphate aluminum sol binder: 4wt% of pseudo-boehmite on a dry basis is mixed with a certain amount of deionized water, and 15wt% (in terms of P2O5) of 85wt% concentrated phosphoric acid is added to the slurry under stirring. Then a certain amount of hydrochloric acid is added, and the pH of the system is controlled to 1.5 to obtain a colorless and transparent phosphate aluminum sol.

[0165] Preparation of mixed molecular sieve slurry: Mix 70wt% of the molecular sieve with a certain amount of deionized water, stir evenly, and then add 1wt% of the La(NO3)3 solution (calculated as La2O3) with a total dry weight to prepare a mixed molecular sieve slurry.

[0166] Preparation of co-catalyst: Under stirring, 10wt% of kaolin and a certain amount of water were mixed and slurried, and phosphorus aluminum sol was added, and stirring was continued for 0.5h, and then the mixed molecular sieve slurry was added and stirred for 0.5h. The solid content of the obtained slurry was 38wt%. After homogenization, the slurry was sprayed and calcined at 600℃ for 2h to obtain the co-catalyst.

[0167] Comparative Example 2

[0168] Dissolve 80g NH4Cl in 1000g water, add 100g (dry basis) crystallized product ZSM-5 molecular sieve (synthesized by amine method, SiO2 / Al2O3=170) to the solution, exchange at 85℃ for 0.5h, filter to obtain filter cake; dissolve 8.9g NH4H2PO4 in 60g water, mix with filter cake, impregnate, and dry; dissolve 31.9g FeSO4·6H2O in 90g water, mix with the above sample, impregnate, and dry, and then calcine at 600℃ for 2 hours to obtain molecular sieve. According to elemental analysis, the chemical composition is 0.1Na2O·0.94Al2O3·5.1P2O5·10.1Fe2O3·84SiO2.

[0169] 0.37 kg of aluminum hydroxide powder (containing 0.28 kg of Al2O3), 0.52 kg of rector clay (0.40 kg on dry basis) and 4.31 kg of deionized water are slurried for 30 minutes, and 2.14 kg of phosphoric acid (calculated as phosphorus pentoxide, containing 1.32 kg of phosphorus pentoxide) are added to the slurry under stirring. The phosphoric acid addition rate is 0.07 kg phosphoric acid / minute / kg of alumina source. The temperature is raised to 70°C, and then reacted at this temperature for 45 minutes to obtain a clay-containing phosphorus-aluminum inorganic binder.

[0170] Take the above molecular sieve, kaolin (solid content 78wt%), diatomite and pseudo-boehmite (solid content 60%, industrial product produced by Shandong Aluminum Plant), add decationized water and water glass (industrial product produced by Qilu Petrochemical Catalyst Plant, SiO2 content 28.9wt%, Na2O content 8.9wt%) and beat for 120 minutes, add hydrochloric acid to adjust the pH value of the slurry to 3.0, beat for 45 minutes, add diammonium hydrogen phosphate solid, and then add clay-containing phosphate aluminum inorganic binder to the slurry, stir for 30 minutes to obtain a slurry with a solid content of 38 weight%, and then spray dry the obtained slurry to obtain microspheres with an average particle diameter of 65 microns, calcine the microspheres at 500°C for 1 hour, and then mix with a 1.5wt% FeCl3·6H2O aqueous solution, react at 60°C for 20 minutes, filter, dry, and then calcine at 500°C for 2 hours to obtain a catalytic cracking promoter.

[0171] In the above-mentioned rector soil, quartz sand is less than 3.5wt%, Al2O3 is 39.0wt%, Fe2O3 is 2.0wt%, Na2O is 0.03wt%, and the solid content is 77wt%.

[0172] Comparative Example 3

[0173] The contents of the components in the catalytic cracking promoter in this comparative example are the same as those in Example 5, and the preparation method is similar to that in Example 5, except that the step of acid-treating the molecular sieve is omitted. The specific preparation process is as follows:

[0174] S1: Mixing the octadent chelating ligand diethylenetriamine penta (methylene phosphonic acid) with the lactic acid solution to prepare a lactic acid solution of the diethylenetriamine penta (methylene phosphonic acid) multidentate chelating ligand, and adding the ethanol solution after mixing evenly to prepare a diethylenetriamine penta (methylene phosphonic acid) ligand solution. The molar concentration of the diethylenetriamine penta (methylene phosphonic acid) in the ligand solution is 0.6 mol / L, the concentration of the lactic acid is 20%, and the concentration of the ethanol is 10%.

[0175] S2: Add samarium chloride and cobalt chloride to a lactic acid solution, add an ethanol solution after they are completely dissolved, and mix them evenly to obtain a precursor solution of a mixed coordination metal. The concentration of lactic acid in the precursor solution is 20%, the concentration of ethanol is 10%, the total molar concentration of the coordination metals (samarium and cobalt) is 0.15 mol / L, and the molar ratio of cobalt chloride to samarium chloride is 1:8.

[0176] S3: Add samarium chloride to the lactic acid solution, add ethanol solution after it is completely dissolved, mix well to obtain a precursor solution of rare earth metals. The concentration of lactic acid in the precursor solution is 20%, the concentration of ethanol is 10%, and the molar concentration of samarium is 0.15 mol / L.

[0177] S4: After exchanging the ZSM-5 molecular sieve and the Y-type molecular sieve with ammonium chloride, the molar content of Na2O in the mixed molecular sieve is reduced to below 0.1wt%.

[0178] S5: Mix the mixed molecular sieve of ZSM-5 molecular sieve and Y-type molecular sieve with deionized water to obtain molecular sieve slurry, heat it to 80°C, add the diethylenetriamine penta (methylene phosphonic acid) ligand solution prepared by S1, stir evenly, add an equal volume of rare earth metal precursor solution prepared by S3, and continue stirring at this temperature for 0.5h. Dry the material obtained after the reaction at 120°C for 12h, and then roast it at 600°C for 3h (100% water vapor is passed in the first 120min of roasting, and air is passed in the last 60min for roasting) to obtain the modified molecular sieve;

[0179] Wherein, the molar ratio of diethylenetriaminepenta(methylenephosphonic acid) to samarium chloride is 4:1.

[0180] S6: Add the hexamethylenediaminetetramethylenephosphonic acid ligand solution obtained in S1 to a high shear dispersing emulsifier, keep the temperature at 40°C, add an equal volume of the mixed coordination metal precursor solution obtained in S2, adjust the pH value of the system to 7, and obtain a binder modifier solution. Add a mixed aqueous solution of aluminum isopropoxide and phosphoric acid (P / Al molar ratio = 6:1) to a high shear dispersing emulsifier, heat to 70°C, adjust the pH to 3.0 for reaction, and after the reaction is completed, a modified aluminum phosphate binder colloid can be obtained. Then mix the modified molecular sieve obtained in S5 with deionized water, add it to a high shear emulsifier, and mix well to obtain a mixed slurry;

[0181] S7: Pseudo-boehmite (peptization index is 25%), kaolin and deionized water are mixed to prepare a matrix slurry.

[0182] S8: Add the mixed slurry prepared in S6 to the base slurry prepared in S7, and continue mixing in a high shear emulsifier for 1 minute, and then spray forming. The spray forming conditions are as follows: the furnace temperature of the spray tower is controlled at 580°C, and the spray exhaust gas temperature is controlled at 160°C. The obtained material is calcined at 600°C for 2 hours to obtain a catalytic cracking promoter.

[0183] The physicochemical properties and catalytic performance of the co-catalyst are specifically shown in Table 1.

[0184] Comparative Example 4

[0185] This comparative example is similar to Example 5, except that no multidentate chelating ligand is added in this comparative example, and the precursor of the coordination metal and the precursor of the rare earth metal are not dissolved by acid and alcohol but by water. The specific preparation process is as follows:

[0186] S1: Add samarium chloride and cobalt chloride into water until they are completely dissolved to obtain a precursor solution of mixed coordinated metals. The total molar concentration of coordinated metals (samarium and cobalt) in the precursor solution is 0.15 mol / L, and the molar ratio of cobalt chloride to samarium chloride is 1:8.

[0187] S2: Add samarium chloride into water and wait for it to completely dissolve to obtain a precursor solution of rare earth metals. The molar concentration of samarium in the precursor solution is 0.15 mol / L.

[0188] S3: After exchanging the ZSM-5 molecular sieve and the Y-type molecular sieve with ammonium chloride, the molar content of Na2O in the mixed molecular sieve is reduced to below 0.1wt%.

[0189] S4: Mix the mixed molecular sieve of ZSM-5 molecular sieve and Y-type molecular sieve with deionized water to obtain molecular sieve slurry, and then add a mixture of dilute hydrochloric acid and oxalic acid (the molar ratio of hydrochloric acid to oxalic acid is 3:1) to the molecular sieve slurry. After adding the acid, the system pH is 1.0, and the temperature is raised to 80°C. After reacting in a reactor with a reflux device for 2 hours until the reaction is completed, the precursor solution of rare earth metals obtained in S2 is added (the amount of samarium chloride added is the same as the amount of samarium chloride added in step S5 of Example 5), and after stirring evenly, continue stirring at this temperature for 0.5 hours. The material obtained after the reaction is dried at 120°C for 12 hours, and then roasted at 600°C for 3 hours (100% water vapor is introduced in the first 120 minutes of roasting, and air is introduced in the last 60 minutes for roasting) to obtain the molecular sieve after acid treatment;

[0190] S5: Add the precursor solution of the mixed coordination metal obtained in S1 (the amount of samarium chloride and cobalt chloride added is the same as the amount of samarium chloride and cobalt chloride added in step S6 in Example 5), a mixed aqueous solution of aluminum isopropoxide and phosphoric acid (P / Al molar ratio = 6:1) to a high shear dispersing emulsifier, heat to 70°C, adjust pH to 3.0 for reaction, and after the reaction is completed, a modified aluminum phosphorus binder colloid can be obtained. Then, the acid-treated molecular sieve obtained in S4 is mixed with deionized water, added to the high shear emulsifier, and mixed evenly to obtain a mixed slurry;

[0191] S6: Pseudo-boehmite (peptization index is 25%), kaolin and deionized water are mixed to prepare a matrix slurry.

[0192] S7: Add the mixed slurry prepared in S5 to the base slurry prepared in S6, and continue mixing in a high shear emulsifier for 1 minute, and then spray forming. The spray forming conditions are that the furnace temperature of the spray tower is controlled at 580°C, and the spray exhaust temperature is controlled at 160°C. The obtained material is calcined at 600°C for 2 hours to obtain a catalytic cracking promoter.

[0193] The physical and chemical properties and catalytic performance of the catalytic cracking promoter prepared in this comparative example are specifically shown in Table 1.

[0194] Comparative Example 5

[0195] This comparative example is similar to Example 5, except that the peptization index of the pseudo-boehmite used is different. The peptization index of the pseudo-boehmite used in this comparative example is 99%.

[0196] The physical and chemical properties and catalytic performance of the catalytic cracking promoter prepared in this comparative example are specifically shown in Table 1.

[0197] Comparative Example 6

[0198] This comparative example is similar to Example 5, the only difference being that different devices are used in the mixing slurry and roasting molding steps. In this comparative example, a stirring reactor is used to replace the high shear emulsifier, and the overtime time is correspondingly extended until the stirring is uniform.

[0199] Comparative Example 7

[0200] This comparative example is similar to Example 6, except that the binder modifier is a mixture of equal amounts of ethylenediaminetetraacetic acid chelated copper and hydroxyethylethylenediaminetriacetic acid chelated lanthanum (in terms of metal oxides, the binder modifier added in this comparative example is equal to that in Example 6). The specific preparation method is as follows:

[0201] The catalytic cracking promoter provided in this comparative example, based on the total weight of the catalytic cracking promoter on a dry basis as 100%, has a ZSM-5 molecular sieve content of 45wt%, a Y-type molecular sieve content of 11wt%, a binder modifier content of 3.0wt%, a pseudo-boehmite (peptization index of 25%) content of 4wt%, a kaolin content of 27wt%, and a binder content of 10wt% (P / Al molar ratio of 6:1).

[0202] The specific preparation method is as follows:

[0203] Ammonium exchange: After exchanging the ZSM-5 molecular sieve and the Y-type molecular sieve with ammonium chloride, the molar content of Na2O in the mixed molecular sieve is reduced to less than 0.1wt%;

[0204] Acid treatment: Mix the mixed molecular sieve after ammonium exchange with deionized water to obtain a molecular sieve slurry, and then add a mixture of dilute hydrochloric acid and oxalic acid (the molar ratio of hydrochloric acid to oxalic acid is 3:1) to the molecular sieve slurry. After adding the acid, the pH of the system is 1.0, and the temperature is raised to 80°C. React in a reactor with a reflux device for 2 hours until the reaction is completed. The material obtained after the reaction is dried at 120°C for 12 hours, and then roasted at 600°C for 3 hours (100% water vapor is passed in the first 120 minutes of roasting, and air is passed in the last 60 minutes for roasting) to obtain an acid-treated molecular sieve;

[0205] Mixed slurry: the calcined molecular sieve obtained in the acid treatment step is mixed with deionized water, and diluted hydrochloric acid is added to stabilize the pH of the system at 1.0; the mixture is added to a high shear emulsifier, and then aluminum hydroxide is added and the temperature is raised to 60° C. After uniform dispersion, aluminum dihydrogen phosphate is added in proportion, and the mixture is kept at 60° C. for rapid reaction for 10 minutes, and then a mixed solution of ethylenediaminetetraacetic acid chelated copper and hydroxyethylethylenediaminetriacetic acid chelated lanthanum (the ratio of the total molar number of copper and lanthanum elements to the molar number of phosphorus elements is 5:1, and the molar ratio of copper to lanthanum is 5:1) is added, and the mixture is continued to react at 60° C. for another 5 minutes to obtain a mixed slurry of aluminum phosphate binder and molecular sieve;

[0206] Calcination molding: add matrix slurry (obtained by uniformly mixing pseudo-boehmite with a peptization index of 25%, kaolin and deionized water) to the mixed slurry of the above-mentioned aluminum phosphate binder and molecular sieve, and continue to emulsify at high speed in a high shear emulsifier for 2 minutes, and then immediately lead out for spray molding and drying. The spray molding conditions are that the furnace temperature of the spray tower is controlled at 580°C, and the spray exhaust temperature is controlled at 160°C. The obtained material is calcined at 600°C for 2 hours to obtain a catalytic cracking aid.

[0207] The physical and chemical properties and catalytic performance of the catalytic cracking promoter are specifically shown in Table 1.

[0208] The physical and chemical properties and catalytic performance of the catalytic cracking promoter prepared in this comparative example are specifically shown in Table 1.

[0209] Table 1 Physical and chemical properties and reaction performance of co-catalysts

[0210]

[0211] It can be seen from the data in the above table that, compared with the comparative example, the catalytic cracking promoter provided by the present invention has higher abrasion resistance, large pore volume and high molecular sieve content, and the yield of the target product of catalytic cracking is high.

[0212] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A catalytic cracking promoter with high thermal wear resistance, characterized in that: including a molecular sieve, a matrix, a binder and a binder modifier; The molecular sieve has an MFI structure and the molecular sieve with a pore diameter less than 0.7 nm accounts for 50wt% to 100wt% of the total molecular sieve; The matrix is ​​composed of a γ-alumina precursor with a peptization index of ≤50% and clay; The binder is made of a phosphorus-containing compound and an aluminum-containing compound; The raw materials of the binder modifier include a multidentate chelating ligand, precursors of at least two coordinated metals, an alcohol and an organic acid; The binder, the binder modifier and the matrix are mixed in a high shear emulsifier.

2. The catalytic cracking promoter with high thermal wear resistance as claimed in claim 1, characterized in that: The catalytic cracking promoter also includes a molecular sieve modifier, which is the same as or different from the binder modifier; preferably, the raw materials of the molecular sieve modifier include a multi-dentate chelating ligand, a precursor of a rare earth coordination metal, an alcohol and an organic acid.

3. The catalytic cracking promoter with high thermal wear resistance as claimed in claim 1 or 2, characterized in that: The multidentate chelating ligand is a bidentate chelating ligand having at least two coordinating atoms, and the coordinating atoms are P, O, or N and O; preferably, the multidentate chelating ligand is selected from any one of aminotri (methylene phosphonic acid), hydroxyethylidene diphosphonic acid, ethylenediamine tetra (methylene phosphonic acid), diethylenetriamine penta (methylene phosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, 2-hydroxyphosphonoacetic acid, bis (1,6-hexamethylenetriamine penta (methylene phosphonic acid), hexamethylenediamine tetra (methylene phosphonic acid), ethylenediaminetetraacetic acid, diethylenetriamine pentaacetic acid and 1,2-ethylenediamine; more preferably, the coordinating atoms in the multidentate chelating ligand are P and O.

4. The catalytic cracking promoter with high thermal wear resistance as claimed in claim 1, wherein in the binder modifier, the precursor of the coordination metal is selected from chlorides, sulfates or nitrates of rare earth metals and transition metals; preferably, the rare earth metal is selected from light rare earth metals.

5. The catalytic cracking promoter with high thermal wear resistance as claimed in claim 4, characterized in that: In the binder modifier, the molar ratio of the transition metal to the rare earth metal is 1:5-10; and the molar ratio of the multi-dentate chelate ligand to the coordination metal is 2-5:

1.

6. The catalytic cracking promoter with high thermal wear resistance as claimed in claim 2, characterized in that: In the molecular sieve modifier, the molar ratio of the multi-dentate chelating ligand to the rare earth coordination metal is 2 to 5:

1.

7. The catalytic cracking promoter with high thermal wear resistance as claimed in claim 1 or 2, characterized in that: The organic acid is one or more of benzoic acid, lactic acid, propionic acid, formic acid, acetic acid, sorbic acid and malic acid; The alcohol is selected from C1-C3 monohydric alcohols, preferably one or more of methanol, ethanol and propanol.

8. The catalytic cracking promoter with high thermal wear resistance as claimed in claim 1, characterized in that: The molar ratio of phosphorus in the phosphorus-containing compound to aluminum in the aluminum-containing compound is 2 to 10:1, preferably the molar ratio of phosphorus in the phosphorus-containing compound to aluminum in the aluminum-containing compound is 4 to 8:1; and / or The peptization index of the γ-alumina precursor is 20% to 30%; preferably, the XRD spectrum of the γ-alumina precursor has characteristic peaks near 2θ of 14°, 28°, 38°, and 49°; and / or The mass ratio of the γ-alumina precursor to the clay is 1:0.5-15, preferably 1:2-9.

9. The catalytic cracking promoter with high thermal wear resistance as claimed in claim 1 or 2, characterized in that: Based on the total dry weight of the catalytic cracking promoter as 100%, the content of the molecular sieve is 20wt% to 70wt%, the content of the matrix is ​​10wt% to 40wt%, the content of the binder is 10wt% to 30wt%, the content of the binder modifier is 1.5wt% to 10wt%, and the content of the molecular sieve modifier is 0wt% to 2wt%.

10. A method for preparing a catalytic cracking promoter with high thermal wear resistance according to any one of claims 1 to 9, characterized in that: The steps include: Acid treatment: a molecular sieve having a Na2O content of ≤0.1wt% is mixed with deionized water to form a molecular sieve slurry, a mixed acid of an organic acid and an inorganic acid is added until the pH of the molecular sieve slurry is ≤2.0 and a reaction is carried out, and after the reaction is completed, the molecular sieve is dried and calcined to obtain an acid-treated molecular sieve; Mixed slurry: the binder modifier and the binder are mixed evenly in a high shear emulsifier, and then the mixture of the acid-treated molecular sieve and deionized water is added and mixed evenly to obtain a mixed slurry; Calcination and molding: adding the matrix slurry to the mixed slurry, and continuing to mix in a high shear emulsifier for 5 minutes, and then spray molding, drying, and calcining to obtain the catalytic cracking promoter with high thermal wear resistance.

11. The preparation method according to claim 10, characterized in that: The preparation of the binder modifier comprises the following steps: Adding alcohol to the organic acid solution of the multi-dentate chelating ligand and mixing well to obtain a multi-dentate chelating ligand solution; Adding alcohol to an organic acid solution containing at least two precursors of coordinated metals, and mixing the mixture to obtain a precursor solution of coordinated metals; Adding the multidentate chelating ligand solution and the precursor solution of the coordination metal into a high shear dispersing emulsifier, and adjusting the pH value of the system to 5-8; Obtain a binder modifier.

12. The preparation method according to claim 10, characterized in that: In the acid treatment step, after the reaction is completed, a step of adding a molecular sieve modifier is also included; preferably, the preparation of the molecular sieve modifier includes the following steps: Adding alcohol to the organic acid solution of the multi-dentate chelating ligand and mixing well to obtain a multi-dentate chelating ligand solution; Adding alcohol to the organic acid solution of the rare earth coordination metal precursor and mixing well to obtain a rare earth metal precursor solution; The multidentate chelate ligand solution and the rare earth metal precursor solution are added into a high shear dispersing emulsifier, and the pH value of the system is adjusted to 5-8 to obtain a molecular sieve modifier.

13. The preparation method according to claim 10, characterized in that: In the acid treatment step, 100% water vapor is introduced during the first 2 / 3 of the roasting time, and air is introduced during the last 1 / 3 of the roasting time.

14. The preparation method according to claim 10, characterized in that: The preparation of the binder comprises the following steps: The mixed aqueous solution of the phosphorus-containing compound and the aluminum-containing compound is added into a high shear emulsifier, heated to 60-80° C., and then adjusted to pH ≤ 4.0 for reaction to obtain the binder.

Citation Information

Patent Citations

  • Catalytic cracking propylene additive and preparation method thereof

    CN102049284B

  • Method for preparing catalytic cracking aid

    CN102794194B

  • Cracking aid for improving lower-carbon olefin concentration

    CN102847551B

  • Catalytic cracking propylene assistant and preparation method thereof

    CN103254925B

  • Preparation method of catalytic cracking promoter

    CN104549445A